University of Utrecht 1636–1676: res ecclesia, res publica and … res pecunia. Issue 1 (2nd January 2016) - van Rinsum, Henk; Koops, Willem
Abstract : The early history of Utrecht University (founded 1636) reflects an emerging public sphere (Habermas's 'bürgerliche öffentlichkeit') of a major town in the Netherlands. This public sphere was a contested field among the different groups establishing and administering the university: university professors, town magistrates and representatives of the newly established Reformed Church and the former dominant Catholic Church. The factionalised magistrates developed a public sphere, while also trying to limit the passionate but destabilising debate concerning the new philosophy of Descartes. They supported the Calvinistic anti-Descartes movement while permitting, and even advocating, the establishment of the new philosophy at the university. They ambivalently protected the academy from the consistory's control while simultaneously trying to safeguard their own (financial) position. It is concluded that the Habermasian framework has to be fleshed out in local histories, such as this case study of Utrecht University, to demonstrate the 'messy' complexities in reality.